2020
DOI: 10.1093/ehjcvp/pvaa039
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing to Support Oral AntiCoagulation adherence in patients with non-valvular Atrial Fibrillation (MISOAC-AF): a randomized clinical trial

Abstract: Aims We aimed to assess the impact of an educational, motivational intervention on the adherence to oral anticoagulation (OAC) in patients with non-valvular atrial fibrillation (AF). Methods and results Hospitalized patients with non-valvular AF who received OAC were randomly assigned to usual medical care or a proactive intervention, comprising motivational interviewing, and tailored counselling on medication adherence. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…This is an ancillary study to MISOAC-AF trial (Motivational Interviewing to Support Oral AntiCoagulation Adherence in patients with non-valvular Atrial Fibrillation, ClinicalTrials.gov identifier: NCT02941978) focusing on patients with AF and DM. The design and main results of the MISOAC-AF registry have been previously published [8,9]. In brief, MISOAC-AF demonstrated the impact of a patient-centered interview on improving patients' adherence to oral anticoagulation (OAC) treatment.…”
Section: Methodsmentioning
confidence: 99%
“…This is an ancillary study to MISOAC-AF trial (Motivational Interviewing to Support Oral AntiCoagulation Adherence in patients with non-valvular Atrial Fibrillation, ClinicalTrials.gov identifier: NCT02941978) focusing on patients with AF and DM. The design and main results of the MISOAC-AF registry have been previously published [8,9]. In brief, MISOAC-AF demonstrated the impact of a patient-centered interview on improving patients' adherence to oral anticoagulation (OAC) treatment.…”
Section: Methodsmentioning
confidence: 99%
“…A recent cross-sectional study demonstrated high non-adherence rates or discontinuation of warfarin (26% and 17% respectively) in 127 young patients (mean age 31.2 years) after valve replacement surgery for rheumatic heart disease with a mean time since surgery of 3.7 years [ 39 ]. In general, adherence to NOACs is superior to VKAs [ 40 ], with one out of three patients who start warfarin for atrial fibrillation discontinuing treatment after one year of therapy [ 41 , 42 , 43 , 44 ]. Adherence to NOACs was also good (≥ 80%) during the two years of follow-up in the NOTE registry.…”
Section: Discussionmentioning
confidence: 99%
“…This is an ancillary study to MISOAC-AF trial (Motivational Interviewing to Support Oral AntiCoagulation Adherence in patients with non-valvular Atrial Fibrillation, ClinicalTrials.gov identi er: NCT02941978) focusing on patients with AF and DM. The design and main results of the MISOAC-AF registry have been previously published 8,9 . In brief, MISOAC-AF demonstrated the impact of a patient-centered interview on improving patients' adherence to oral anticoagulation (OAC) treatment.…”
Section: Methodsmentioning
confidence: 99%